Manajemen strategi bank syariah: menemukan keseimbangan antara profitabilittas dan prinsip syariah - afanin, alfenda nafiah (Maliki Interdisciplinary Journal, 2025)
Balancing financial returns with Shariah principles is a key challenge in the strategic management of Islamic banking is a key challenge in the strategic management of Islamic banking. To achieve this, the bank needs to conduct an in-depth analysis of its internal and external environment, develop goals that are in line with Islamic values and internal and external environment, set objectives that are in line with Islamic values, design appropriate strategies, and periodically evaluate performance. By Thus, Islamic banking can grow sustainably, maintain customer customer trust, and contribute positively to society. Bank face the challenge of balancing profitability and compliance with sharia principles. with sharia principles. This research aims to identify to overcome these challenges through literature review and case analysis. case analysis. The research emphasizes the importance of aligning the vision, mission and strategies with sharia values, as well as the role of risk management in maintaining the sustainability and reputation of Islamic banks. sustainability and reputation of Islamic banks.